033 Effect of ocrelizumab on upper limb function in patients with primary progressive multiple sclerosis (PPMS) in the oratorio study (ENCORE). Issue 6 (24th May 2018) - Fox, Edward; Markowitz, Clyde; Applebee, Angela; Montalban, Xavier; Wolinsky, Jerry S; Belachew, Shebeshih; Fiore, Damian; Han, Jian; Musch, Bruno; Giovannoni, Gavin
Abstract : Introduction: Upper limb (UL) functional impairment is prevalent among PPMS patients and alters quality of life. The nine-hole peg test (9HPT) is a validated quantitative assessment of UL function in MS. Methods: 9HPT was administered at baseline and every 12 weeks until study end. The average 9HPT-times from two trials of dominant- and non-dominant-hands were compared; the hand with the lower baseline time was termed 'better-hand', and the hand with the higher baseline time was termed 'worse-hand'. Average dominant- and non-dominant-hand times were combined and termed 'both-hands'. Analyses included time-to-confirmed progression (CP) in hand function, defined as ≥15%, ≥20% or ≥25% increase in 9HPT-time from baseline, confirmed at 12- and 24 weeks, and change in 9HPT-time from baseline to Week-120. Results: Compared with placebo, ocrelizumab reduced the time-to 12- and 24-week-CP of ≥15% increase on 9HPT by 37% (hazard ratio [HR]=0.627; p=0.001) and 39% (HR=0.607; p=0.002) for both-hands, 30% (HR=0.699; p=0.011) and 40% (HR=0.599; p<0.001) for better-hand and 29% (HR=0.705; p=0.016) and 28% (HR=0.717; p=0.040) for worse-hand. The time-to 12- and 24-week-CP of ≥20% increase on 9HPT was reduced by 44% (HR=0.561; p<0.001) and 45% (HR=0.545; p<0.001) for both-hands, 28% (HR=0.723; p=0.046) and 35% (HR=0.646; p=0.014) for better-hand and 37% (HR=0.632; p=0.005) and 40% (HR=0.599; p=0.004) for worse-hand. Ocrelizumab also reduced the time-to 12- and 24-week-CP of ≥25% increase on 9HPT by 48% (HR=0.520; p<0.001) and 49% (HR=0.507; p<0.001) for both-hands, 30% (HR=0.698; p=0.048) and 39% (HR=0.613; p=0.015) for better-hand, and 48% (HR=0.521; p<0.001) and 42% (HR=0.578; p=0.004) for worse-hand. At week-120, the increase from baseline 9HPT-time for both-hands and worse-hand was significantly smaller with ocrelizumab vs placebo (p<0.001 and p=0.041, respectively); for better hand, the increase was smaller with ocrelizumab; difference was not significant (p=0.056). Conclusion: Ocrelizumab treatment lowered the risk of progression of upper extremity disability, measured by 9HPT, compared with placebo in PPMS patients.